2021
DOI: 10.1080/19768354.2021.1953142
|View full text |Cite
|
Sign up to set email alerts
|

CKS1B promotes the progression of hepatocellular carcinoma by activating JAK/STAT3 signal pathway

Abstract: Hepatocellular carcinoma (HCC) is a malignancy of considerable concern due to its continuous increase in morbidity and mortality. This study attempts to identify the molecules that play a key role in the progression of HCC, explore its potential mechanism, and provide more target choices for targeted therapy. Using overexpression plasmid and shRNA, CKS1B was respectively overexpressed and knocked down to explore its biological function roles in HCC progression and development. MTT and colony formation assays s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Moreover, flow cytometry revealed a higher rate of apoptosis ovarian cancer cells that had been treated with si-CKS1B; moreover, the levels of Bax and cleaved caspase 3 were higher. Similarly, Liu et al [16] reported that the silencing of CKS1B markedly suppressed the survival and viability of hepatocellular carcinoma cells, thus suppressing the development and metastasis of hepatocellular carcinoma. In lung adenocarcinoma, CKS1B serves as a vital regulator involved in promoting the proliferation of tumors [17].…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, flow cytometry revealed a higher rate of apoptosis ovarian cancer cells that had been treated with si-CKS1B; moreover, the levels of Bax and cleaved caspase 3 were higher. Similarly, Liu et al [16] reported that the silencing of CKS1B markedly suppressed the survival and viability of hepatocellular carcinoma cells, thus suppressing the development and metastasis of hepatocellular carcinoma. In lung adenocarcinoma, CKS1B serves as a vital regulator involved in promoting the proliferation of tumors [17].…”
Section: Discussionmentioning
confidence: 87%
“…In depth study implied that the loss of EPN3 might suppress NSCLC cell malignant phenotype via inactivating the JAK1/2‐STAT3 pathway. As we known, the aberrantly activation of the JAK/STAT3 pathway is involved in the malignant development of multiple cancers, such as hepatocellular carcinoma, pancreatic cancer, gastric cancer as well as breast cancer, and so on 41–44 . Similarly, several literatures have confirmed that the activation of the JAK/STAT3 pathway promotes the malignant development of NSCLC 45–47 .…”
Section: Discussionmentioning
confidence: 88%
“…As we known, the aberrantly activation of the JAK/STAT3 pathway is involved in the malignant development of multiple cancers, such as hepatocellular carcinoma, pancreatic cancer, gastric cancer as well as breast cancer, and so on. [41][42][43][44] Similarly, several literatures have confirmed that the activation of the JAK/STAT3 pathway promotes the malignant development of NSCLC. [45][46][47] The treatment targeting the JAK/STAT3 pathway has been proposed to be a promising regimen for tumors.…”
Section: Loss Of Epn3 Might Suppress the In Vivo Growth Of Nsclc Cell...mentioning
confidence: 87%
“…Low expression of Receptor coactivator 3 (NCOA3) may lead to decreased differentiation potential of embryonic stem cells in vitro and in vivo [ 24 ]. CKS1B regulates cell cycle processes by engaging with cyclin-dependent kinase (CDK) and SCF complex to affect cell proliferation [ 25 ]. MDM2, an E3 ubiquitin ligase, plays a crucial role in the differentiation of various cell types, including osteoblasts and myoblasts [ 26 ].…”
Section: Resultsmentioning
confidence: 99%